Transformasi Mata Kuliah Bahasa Indonesia dalam Membangun Literasi Akademik Mahasiswa di Perguruan Tinggi - Muhammad Taskil; Setfano Ade Nong Fecy; Ryani Ryani; Yeremias Bardi (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2026)
This study examines the implementation of Indonesian Language learning in higher education as a foundation for developing students’ academic literacy within an Outcome Based Education (OBE) framework. The research is motivated by serious concerns regarding students’ low academic writing ability, weak critical reading skills, and inconsistent use of academic language, which hinder the formation of academic culture at universities. The objective of this study is to describe and interpret the learning process, challenges, and outcomes of Indonesian Language courses in fostering academic literacy. This research employed a qualitative descriptive approach conducted intensively over a three-week period. Data were collected through classroom observations, in depth interviews with lecturers and students, and document analysis of lesson plans, teaching materials, and students’ academic assignments. The findings reveal that although the course design conceptually aligns with OBE principles, its classroom implementation has not fully emphasized reflective processes, critical engagement, and consistent academic language practice. Learning activities tend to focus on task completion rather than on the development of academic thinking processes. The study implies that Indonesian Language learning should be strengthened through reflective, contextual, and process oriented strategies to enhance students’ academic literacy and academic identity. These findings contribute theoretically to studies on academic literacy and practically to the improvement of Indonesian Language instruction in higher education.